Neoroprotective effects of tocotrienol-rich fraction and α-tocopherol of vitamin E against glutamate toxicity on astrocyte-neuronal mono-culture and co-culture systems - Yap, Hui Min (2013)
Elevated concentration of glutamate, also known as glutamate neurotoxicity, is the major contributor to pathological cell death in nervous system. It has been suggested to play a key role in neurodegenerative diseases. In recent studies, palm tocotrienolrich fraction (TRF) has been shown to exhibit better neuroprotection than alphatocopherol against glutamate toxicity. It was also shown to exert potent antioxidant, anti-inflammatory, anticancer and cholesterol-lowering properties. The main objective of this study is to elucidate the effects of TRF and α-tocopherol pretreatment and post-treatment against glutamate toxicity in astrocyte and neuronal cell. Besides, the synergism between astrocyte and neuronal cell in protecting glutamate neurotoxicity with the supplementation of TRF and α-tocopherol were assessed through co-culture model. Astrocyte and neuronal cell in this study were exposed to high concentration of glutamate. The behavior of cell lines responding to glutamate toxicity was determined through dose-response and time course study. Astrocyte and neuronal cell were subjected to glutamate injury before or after TRF and α-tocopherol treatment. The effects of TRF and α-tocopherol against glutamate toxicity were assessed through MTT cell viability assay, glutathione production, neuron-specific enolase (NSE) expression study and mode of cell death study. The expression of NSE was examined through reverse-transcriptase real time polymerase chain reaction (RT- qPCR) while mode of cell death was determined through acridine orange/propidium iodide (AOPI) assay. The morphological changes due to glutamate toxicity and TRF and α-tocopherol treatments were observed under fluorescence microscope. Statistical analysis was performed using one way ANOVA with SPSS 17.0. The concentration of glutamate needed to cause 50% cell death for astrocyte and neuronal cell were 230 mM and 80 mM, respectively. The concentrations of glutamate used throughout this study were only meant to cause injury to the cells. Glutamate with concentration of 60 mM and 180 mM were used to cause injury in neuronal cell and astrocyte respectively. Generally, TRF and α-tocopherol improved the cell viability of glutamate-injured neuronal cell and astrocyte by approximately 10%. In co-culture model study, TRF and α-tocopherol post-treatments provided nearly complete protection toward glutamate toxicity. Besides, TRF and α-tocopherol post-treatments were showed to restore the glutathione content upon glutamate injury. In astrocyte, TRF pre-treatment inhibited the decrease of glutathione content. In the presence of astrocyte, TRF and α-tocopherol pre-treatments inhibited decrease of glutathione content in neuronal cell which was not observed in mono-culture model. In addition, 300 ng/mL TRF and α-tocopherol completely restored glutathione production in glutamate-injured neuronal cell in co-culture model. TRF and α-tocopherol generally increased the percentage of healthy cell and decreased the percentage of necrotic cell in both cell lines as well as in co-culture model. TRF and α-tocopherol post-treatments with concentration of 100 to 300 ng/mL decreased the percentage of necrotic cell in glutamate-injured astrocyte and neuronal cell more than 10%. Downregulation or suppression of NSE expression was observed in glutamate induced astrocyte and neuronal cell as well as in co-culture model. In conclusion, TRF and α-tocopherol provided protection and recovery properties toward astrocyte and neuronal cell against glutamate toxicity. Similar effects between TRF and α-tocopherol were found in both astrocyte and neuronal cell against glutamate toxicity. Co-culture model in this study has demonstrated synergistic properties of astrocytes and neuronal cell. Supplementation of TRF and α-tocopherol in co-culture system further improved the recovery process and protection of astrocytes and neuronal cells compared to mono-culture.